Moderating Role of Cause Related Marketing Campaign Between Attitude Towards Products and Purchase Intention: An Experimental Analysis - Gadhavi, Dharmesh D.; Shukla, Yupal S.; Patel, Jayesh D. (Indian Journal of Marketing, 2014)
Cause related marketing (CrM), being a most common form of promotion, impacts a consumer’s choice and is continuously receiving a considerable attention. For any enterprise, cause related marketing builds on marketing and charity to achieve an improvement either in sales volume or image or attitude or purchase intention (PI). Therefore, the purpose of this study is to ascertain the impact of cause related marketing campaign on attitude towards product-purchase intention relationship. For this, 140 consumers were contacted through convenience sampling method for a pre-experimental causal study. A cause related marketing campaign in the form of an advertisement was shown to 70 participants (male and female) who were above 18 years of age, residing in cities of Gujarat. Multiple regression was used to measure their attitude towards products (PI). The study’s findings highlight that companies practicing CrM can enhance consumers’ purchase intentions.